Development and application of a novel in vivo overload model of the Achilles tendon in rat. (April 2023) - Gains, Connor Charles; Giannapoulos, Antonios; Zamboulis, Danae Emilie; Lopez-Tremoleda, Jordi; Screen, Hazel R.C.
Abstract: Repetitive overload is a primary factor in tendon injury, causing progressive accumulation of matrix damage concurrent with a cellular response. However, it remains unclear how these events occur at the initial stages of the disease, making it difficult to identify appropriate treatment approaches. Here, we describe the development of a new model to cyclically load the Achilles tendon (AT) of rats in vivo and investigate the initial structural and cellular responses. The model utilizes controlled dorsiflexion of the ankle joint applied near maximal dorsiflexion, for 10, 000 cycles at 3 Hz. Animals were subjected to a single bout of in vivo loading under anaesthesia, and either culled immediately (without recovery from anaesthesia), or 48 h or 4-weeks post-loading. Macro strains were assessed in cadavers, whilst tendon specific microdamage was assessed through collagen-hybridizing peptide (CHP) immunohistochemistry which highlighted a significant rise in CHP staining in loaded ATs compared to contralateral controls, indicating an accumulation of overload-induced damage. Staining for pro-inflammatory mediators (IL-6 and COX-2) and matrix degradation markers (MMP-3 and -13) also suggests an initial cellular response to overload. Model validation confirmed our approach was able to explore early overload-induced damage within the AT, with microdamage present and no evidence of broader musculoskeletal damage. The new model may be implemented to map the progression of tendinopathy in the AT, and thus study potential therapeutic interventions.